Threads of the Past: Methodological Tools for Reconstructing the Collective Memory of Peasant Organizations. UPANACIONAL y UPIAV Cases. (Revista Rupturas, 2024)
This article provides methodological recommendations for reconstructing collective memory in social organizations. Reconstructing collective memory is crucial for comprehending the history and identity of social organizations, preserving their legacy, and enhancing their representativeness. The study is based on collaborative research with peasant unions in Costa Rica, employing a mixed-method approach of surveys, in-depth interviews, and documentary analysis. The shortage of studies and methodological frameworks in this area underscores the need for clear and practical recommendations. Some recommendations include building trust and empathy with participants keeping reflective records to enhance understanding of the social phenomenon and facilitating the replication of the methodology. Furthermore, it is crucial to maintain a balance between flexibility and rigor to ensure adaptability to different contexts and enable the extrapolation of the methodology to similar groups.
Keywords: Peasant unions; mixed approach; extrapolation of methodology; permanence; group identity